(untitled) (Asian Journal of Social Science Studies, 2022)
Distance education differs from normal face-to-face classroom situation in terms of a learner or teacher’s physical presence. It is crucial for the distance teachers to provide optimal learning support to ODLs (open distance learners) and prepare them for educational changes. The use of Web-Mobile Platforms (WMPs); Edmodo and Telegram in English language learning-acquisition among the undergraduate ODLs enabled learners and educators to stay connected regardless of physical space and time constraint. This study aims to generate insights and sharing through online questionnaire on Edmodo and Telegram to seek and identify learners’ perceptions in terms of language learning-acquisition process in both contexts. The WMPs were used to accommodate learners’ language learning materials and online discussion forums thus functioned as the scaffolding to facilitate learners’ language learning-acquisition process. The study employs purposively sampling involving eleven undergraduate ODLs from a Malaysian university. The findings are presented in a narrative manner to illustrate the emerging themes and the pedagogical implications pertaining to how the WMPs provided learners access to English learning resources beyond the classroom learning time and opportunities to interact with their peers suggesting practicality and convenient ways of engaging in language learning-acquisition via the WMPs while complementing the existing face-to-face learning mode.